2022
DOI: 10.3389/fcvm.2022.935103
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Left Atrial Strain in Heart Failure: A Systematic Review and Meta-Analysis

Abstract: BackgroundHeart failure (HF) is a global health problem with high morbidity and mortality. Recently, the association between peak atrial longitudinal strain (PALS) and clinical outcomes of HF has gained increasing attention. Our aim was to systematically assess the prognostic value of PALS for adverse events in HF.MethodsPubMed, Embase, and Scopus databases were systematically searched from inception to 30 April 2022. Studies in which PALS was assessed to predict adverse outcomes in adult patients with HF were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…PALS has been identified as a sensitive prognostic marker in many diseases including hypertension, diabetes, chronic renal disease, atrial fibrillation, cardiotoxicity, heart failure, and valvular heart disease. 12,[39][40][41] PALS has also been identified as a predictor of cardiovascular morbidity and mortality in the general population. 42 These disease states introduce cardiovascular pressure and volume overload or arrhythmic insult that can result in adverse atrial myocardial tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PALS has been identified as a sensitive prognostic marker in many diseases including hypertension, diabetes, chronic renal disease, atrial fibrillation, cardiotoxicity, heart failure, and valvular heart disease. 12,[39][40][41] PALS has also been identified as a predictor of cardiovascular morbidity and mortality in the general population. 42 These disease states introduce cardiovascular pressure and volume overload or arrhythmic insult that can result in adverse atrial myocardial tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…A normal reference range for reservoir strain of 38%−41% has been shown in a previous meta‐analysis of healthy adults 11 . The prognostic value of PALS has been demonstrated in several clinical scenarios including cardiovascular events and heart failure 12,13 . There is now a growing body of evidence on the prognostic value of PALS in patients with AS.…”
Section: Introductionmentioning
confidence: 93%
“…Trying to revert the LA remodeling process by improving the LA structure and function is becoming an important goal in ICM management. This is because LA size and function have both emerged as prognostic factors in the general population and in patients with ICM ( 11 , 32 , 33 ). Exercise training has well proven the anti-remodeling effects in the post-ischemic LV ( 34 ), which are among the mechanisms through which exercise favorably impacts ICM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that the reservoir strain, which is often expressed as the peak atrial longitudinal strain (PALS), is impaired in a wide spectrum of cardiovascular conditions, with the highest degree of dysfunction being observed in patients with heart failure (HF) with both reduced and preserved ejection fractions (EF) ( 7 ). The impairment of PALS has been associated with a reduced exercise tolerance ( 8 ), a greater risk of atrial fibrillation insurgency ( 9 ), and a poor outcome ( 10 , 11 ). Similarly to PALS, the peak atrial contraction strain (PACS), reflecting the booster phase of the LA, has also recently been shown to predict survival in patients with cardiovascular diseases ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that impaired LA strain is associated with poor outcomes in patients with myocardial infarction, hypertrophic cardiomyopathy, valvular heart diseases, and heart failure as well as in the general population [ 13 14 28 29 30 31 ]. Schneider et al [ 32 ] demonstrated that the recovery of biatrial function by feature-tracking CMR strain analyses after acute myocarditis was independent of the clinical presentation.…”
Section: Discussionmentioning
confidence: 99%